THE ROLE OF HATOBANGON IN WAQF LAND DISPUTE RESOLUTION: A SOLUTION FOR RURAL CUSTOMARY CONFLICT IN BANGUN PURBA - Nst, Abd Mutholib; Mukhsin, Abd (Universitas Islam Negeri Alauddin Makassar, 2024)
This article aims to explore the role of Hatobangon, a respected traditional figure, in resolving waqf land disputes in Bangun Purba village, Kecamatan Lembah Sorik Marapi, Kabupaten Mandailing Natal. Specifically, it examines the effectiveness of Hatobangon as a mediator within the customary dispute resolution system and identifies the factors influencing their success in maintaining community harmony. The study employs a qualitative approach, utilizing field observations, in-depth interviews with key stakeholders, including Hatobangon leaders and community members, and a review of relevant local regulations and customary practices. Data were analyzed through thematic analysis to uncover patterns in how Hatobangon handles waqf land disputes and the challenges encountered in the process. The findings indicate that Hatobangon plays a central role in mediating disputes by combining customary law and social considerations. However, the effectiveness of this mediation process is hampered by several factors, including inadequate facilities, limited resources, and a lack of public trust in the customary dispute resolution mechanism. Despite these challenges, Hatobangon remains a key figure in ensuring that the outcomes of disputes reflect local cultural values and preserve community cohesion. This study provides new insights into the rarely examined role of Hatobangon in resolving waqf land disputes, highlighting the intersection of customary law and Islamic principles in rural conflict resolution. It adds to the body of literature on indigenous dispute mechanisms by focusing on the unique socio-cultural dynamics of Bangun Purba village. The research suggests that enhancing the resources and capacity of Hatobangon could improve the efficiency of dispute resolution in rural areas. Furthermore, increased community education and formalization of the waqf land dispute mechanism could strengthen public trust in this customary system, promoting social harmony and sustainable land management practices.